Phenotypical expression of reduced mobility during limb ontogeny in frogs: The knee-joint case - Ponssa, María Laura (2016)
Movement is one of the most important epigenetic factors for normal development of the musculoskeletal system, particularly during genesis and joint development. Studies regarding alterations to embryonic mobility, performed on anurans, chickens and mammals, report important phenotypical similarities as a result of the reduction or absence of this stimulus. The precise stage of development at which the stimulus modification generates phenotypic modifications however, is yet to be determined. In this work we explore whether the developmental effects of abnormal mobility can appear at any time during development or whether they begin to express themselves in particular phases of tadpole ontogeny. We conducted five experiments that showed that morphological abnormalities are not visible until Stages 40-42. Morphology in earlier stages remains normal, probably due to the fact that the bones/muscles/tendons have not yet developed and therefore are not affected by immobilization. These results suggest the existence of a specific period of phenotypical expression in which normal limb movement is necessary for the correct development of the joint tissue framework.